Home Purchase Decision Support System Using the Brown-Gibson Method - Rita Frances (Institute of Computer Science (IOCS), 2021)
thesis. The application program was built by applying the Brown-Gibson method which is capable of measuring both qualitative and In making a decision to buy a house, a buyer will consider a variety of complex criteria, such as qualitative (non-numeric) and quantitative (numeric) criteria to get the best decision. To simplify the process, a home purchase decision-making application program was created in this quantitative criteria. The algorithms in the Brown-Gibson method used in this application program include: